Price Dynamics in the Eastern Caribbean - Duttagupta, Rupa (IMF Working Papers; Working Paper ;, 2008)
The Eastern Caribbean Currency Union (ECCU) countries share a common currency, the EC dollar, which has been pegged to the U.S. dollar at the same rate for more than three decades. This paper examines the influence of the peg on ECCU price stability, and analyzes whether absolute Purchasing Power Parity (PPP) holds within the currency union. It shows that U.S. price stability has helped anchor price movement in the ECCU. As the same time, inflation in the ECCU is not entirely imported from the U.S., and has some domestic policy content. In addition, deviation from PPP within the ECCU can be attributed to persistent price dispersion of nontradables.